Analytical study on the 3D-printed structure and mechanical properties of basalt fiber-reinforced PLA composites using X-ray microscopy - Yu, Siwon; Hwang, Yun Hyeong; Hwang, Jun Yeon; Hong, Soon Hyung (ELSEVIER SCI LTD, 2019)
A high-resolution X-ray microscope was used to quantitate the internal morphological characteristics of 3D-printed, basalt-fiber-reinforced PLA composites. 3D-printed composites have microstructures and mechanical properties that are distinct from those of conventional mold-pressed composites. One such distinction lies in the presence of voids, which form naturally during 3D printing. All of the composite components, including the fiber, the matrix, and the aforementioned voids were oriented parallel to the printing direction. The mechanical properties of the final composites were also greatly impacted by their microstructural characteristics, including fiber length, fiber orientation, and the presence of voids. It was also confirmed that the voids generated during the 3D printing process can be classified into two types (inter- and inner-filament voids), whose shapes, sizes, and distributions are completely different from each other, and that they clearly have a decisive influence on the remarkable differences in the strength of the composites.
Keywords: COMPUTED-TOMOGRAPHY; CARBON-FIBER; FAILURE